Determinants of rural poverty: The dynamics of production, technology, and price - Mellor, John W. (International Food Policy Research Institute, 1985)
Two related dynamic forces-productivity-increasing technological change in agriculture and changing food prices-dominate the current controversy about rural poverty. The interacting effects of these forces vary with the technical characteristics of the land, the institutional controls of rents from land and access to other resources, and the economies of acale associated with the new technology.